Szatan - duch powietrza w nauce Bazylego Wielkiego - Osek, Ewa (Vox Patrum, 2002)
This article concerns Saint Basil's demonology and it consists of three parts: 1. The relation of Satan to material world; 2. The atmosphere as a piece of activity of fallen angels; 3. The purpose of devil’s machinations. The references to Satan occur in many writings of Saint Basil, but most important passage can be found in his sermon.